2021
DOI: 10.3389/fpsyg.2021.643109
|View full text |Cite|
|
Sign up to set email alerts
|

Individual, Sociodemographic, and Environmental Factors Related to Physical Activity During the Spring 2020 COVID-19 Lockdown

Abstract: Background: Research has shown important between-individual variations in physical activity (PA) during the COVID-19 lockdown.Objectives: The objectives of this is study are to examine the individual, sociodemographic, and environmental factors related to PA during the spring 2020 COVID-19 lockdown in France and to explore the mediating and moderating role of intention and self-efficacy toward PA in the relationships between sociodemographic/environmental variables and PA.Design: In this cross-sectional study,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
1
8
1
Order By: Relevance
“…These findings support our reasoning that intrinsic motivation may not support PA engagement in situations when exercise does not elicit positive affective experiences and might explain why recent studies have not found intrinsic motivation to be protective against physical activity declines during COVID-19 (see Petersen et al, 2021 ; Rhodes et al, 2020 ; Teran-Escobar et al, 2021 ; Volz et al, 2021 ). Furthermore, findings revealed that there may even be affective repercussions in these situations, especially for individuals who typically exercise for inherent rewards (e.g., enjoyment, interest).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings support our reasoning that intrinsic motivation may not support PA engagement in situations when exercise does not elicit positive affective experiences and might explain why recent studies have not found intrinsic motivation to be protective against physical activity declines during COVID-19 (see Petersen et al, 2021 ; Rhodes et al, 2020 ; Teran-Escobar et al, 2021 ; Volz et al, 2021 ). Furthermore, findings revealed that there may even be affective repercussions in these situations, especially for individuals who typically exercise for inherent rewards (e.g., enjoyment, interest).…”
Section: Discussionsupporting
confidence: 85%
“…These studies consistently found that higher levels of self-efficacy (i.e., one’s confidence in one’s ability to successfully perform a behavior) and identified regulation (i.e., finding personal utility or importance in PA) were protective of PA engagement during this period of disruption ( Petersen et al, 2021 ; Rhodes et al, 2020 ; Volz et al, 2021 ). However, these studies did not find an association between intrinsic motivation–doing an activity for its inherent rewards–or related constructs (e.g., affective judgments) and PA engagement ( Petersen et al, 2021 ; Rhodes et al, 2020 ; Teran-Escobar et al, 2021 ; Volz et al, 2021 ). This finding was unexpected given the wealth of support for intrinsic motivation as a sustainable form of motivation for long-term engagement in PA (see Ng et al, 2012 and Teixeira et al, 2012 for meta- and systematic analyses) and warrants further examination of factors that might impact the association between intrinsic motivation and PA.…”
mentioning
confidence: 94%
“…The result of the COVID-19 pandemic has drastically disrupted routines in adults and children around the globe ranging from commuting behaviours to recreational habits (Maltagliati et al, 2020). This has had a subsequent impact on people's physical activity (PA) routines, due to government level restrictions put in place to stop the spread of the virus (Cheval et al, 2020;Di Corrado et al, 2020, p. 7,8;Dunton et al, 2020;Teran-Escobar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not the case, as contextual factors explain additional variance in behavior once individual cognitions are controlled. For example, intention and self-efficacy only partially mediate the relationships between contextual variables (sociodemographic, health-related, interpersonal and environmental) and physical activity (e.g., Teran-Escobar et al, 2021;Sniehotta et al, 2013). Therefore, the sufficiency hypothesis is not sufficient to explain physical activity.…”
Section: "I Am Fatigued Of Being Stigmatized": On the Need To Investi...mentioning
confidence: 99%